Komparasi Efektivitas Platform Peta Digital dalam Upaya Komunikasi Risiko Bencana Banjir di Daerah Aliran Sungai Ciliwung - Arachman, Fauzi Ramadhoan; Setiawan, Cahyadi; Anindhita, Wiratri (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2024)
This research conducts a qualitative comparative analysis of three digital map platforms for flood risk communication in the Ciliwung River Basin: ArcGIS StoryMaps, Government Portals, and PetaBencana.id. Using literature review and content analysis, each platform's effectiveness was evaluated based on its relevance within the disaster management cycle. The findings show they are complementary; StoryMaps excels at pre-disaster education, Government Portals provide official early warnings, and PetaBencana.id is vital for real-time situational awareness. Information fragmentation on government portals is a key weakness. The study recommends an integrated portal combining official sensor data with crowdsourced data to create a synergistic risk communication ecosystem.